The main principles of foreign language tests - Zhukova, Tetiana; Жукова, Тетяна Василівна; Жукова, Татьяна Васильевна (My University, 2019)
Testing creates great opportunities for the organization of effective and quality control in language learning that can ensure successful achievement of the learning objectives. All diagnostic tools as well as language tests are designed to measure students' achievements and learning outcomes. Assessing the general English proficiency of test takers is a challenging and demanding issue as “it includes various interacting components and subcomponents such as reading, speaking, listening, and writing”
Keywords: testing; validity; test format; language